2021
DOI: 10.1021/acs.jpcc.1c01882
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of PdO/Al2O3 in Liquid Cyclohexane Followed In Situ by ATR-IR, High-Energy XRD, and XAS

Abstract: Supported Pd-based catalysts used in heterogeneously catalyzed liquid phase processes often undergo an activation step through reduction of the oxide phase or of the oxidic passivation layer prior to reaction. An oxidized Pd/Al2O3 catalyst was reduced by using H2-saturated cyclohexane at 70 °C, and reduction was followed in real time by attenuated total reflection infrared spectroscopy (ATR-IR), high-energy X-ray diffraction (XRD), and quick scanning X-ray absorption spectroscopy (XAS) to obtain the perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…At 30 °C, the fraction of PdO decreased below 10% within 150 s in the reducing flow (Figure S11) and was replaced by the spectrum of hydrides through a short period (ca. 60 s) of Pd 0 as already observed before …”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…At 30 °C, the fraction of PdO decreased below 10% within 150 s in the reducing flow (Figure S11) and was replaced by the spectrum of hydrides through a short period (ca. 60 s) of Pd 0 as already observed before …”
Section: Resultssupporting
confidence: 84%
“…60 s) of Pd 0 as already observed before. 22 After reduction at 30 °C, the catalyst was heated to 160 °C to enable observation of desorption of the hydrides by XAS, similar to TPR-1 in Figure 2. Finally, the gas flow was switched to He to obtain the reference spectrum of the bare Pd nanoparticles and the sample was cooled to 30 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At open circuit potential (OCP) and +0.1 V, weak vibration bands located at ~787 and 1015 cm −1 , which can be assigned to the vibration mode of δ (C-C≡N) and r (CH 3 ) in MeCN, respectively, were observed 31 . In addition, the vibration band at 2098 cm −1 originates from the emergence of Pd–H stretching mode 32 , 33 . Along with increasing potential (more negative than +0.1 V), the vibration intensities of δ (C-C≡N), CH 3 and Pd–H are gradually strengthened, suggesting the gradually increased surface coverage of MeCN and H on the surface of Pd/C catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…62 The spectra were dominated by metallic Pd (2.5 Å in R space), but a contribution of PdO (1.5 Å in R space) was clearly visible. 63,64 The spectra of the samples milled in hydrogen showed a decreased contribution of PdO, while the primary peak for Pd−Pd bonds at 2.5 Å increased in intensity for Pd/Al 2 O 3 and slightly shifted to a higher bond distance for both catalysts from 2.54 to 2.57 Å. The intensity shifts indicated that hydrogen milling created a sufficiently reducing environment to reduce any oxidized Pd in situ; for Pd 04 /SiO 2 , the Pd present in the fresh sample had a lower PdO concentration, which is why a significant increase in the peak intensity -was not observed, but a slight hydride shift still occurred.…”
mentioning
confidence: 99%